2016
DOI: 10.1002/2016gc006312
|View full text |Cite
|
Sign up to set email alerts
|

Velocity structure near IODP Hole U1309D, Atlantis Massif, from waveform inversion of streamer data and borehole measurements

Abstract: Seismic full waveform inversion (FWI) is a promising method for determining the detailed velocity structure of the igneous oceanic crust, especially for locations such as the Mid‐Atlantic Ridge with significant lateral heterogeneity and seafloor topography. We examine the accuracy of FWI by inverting, after downward continuation to datum just above the seafloor, a multichannel seismic (MCS) profile from Atlantis Massif oceanic core complex at 30°N that passes close to Integrated Ocean Drilling Program (IODP) H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 87 publications
4
41
0
Order By: Relevance
“…Atlantis massif (MAR, 30°N) is an inside‐corner OCC bounded by a transform fault and consisting of a large gabbroic core surrounded by serpentinized peridotites (e.g., Blackman et al, ; Harding et al, ). Collins et al () found that seismicity at the Atlantis massif (~55 events per day) was concentrated in the axial valley rather than beneath the massif itself, which is located outboard of the axial valley on the inside corner of a ridge transform intersection.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantis massif (MAR, 30°N) is an inside‐corner OCC bounded by a transform fault and consisting of a large gabbroic core surrounded by serpentinized peridotites (e.g., Blackman et al, ; Harding et al, ). Collins et al () found that seismicity at the Atlantis massif (~55 events per day) was concentrated in the axial valley rather than beneath the massif itself, which is located outboard of the axial valley on the inside corner of a ridge transform intersection.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the inversion result suffers from velocity-depth ambiguity. Streamer TTT exploits the dense and even spatial distribution of MCS data and is further improved upon by DC, which allows for the inclusion of shallower refractions that were only previously obtainable using either seafloor receivers and sources (Henig, 2013). It is important to notice that these highlighted phases would correspond to ray paths in the upper region of the subseafloor section.…”
Section: Discussionmentioning
confidence: 99%
“…All ultramafic samples analyzed in this study come from the detachment shear zone that is documented to be 100 m thick at the southern wall (Karson et al, ; Schroeder & John, ). On the contrary, the detachment shear zone is thin (<20 m) at the Central Dome (Harding et al, ), and the mafic samples come mostly from the deeper and broader deformation zone, well below the detachment shear zone. The experimental rig that we used for the physical properties measurements requires cylindrical samples of 5‐cm diameter and ~2‐cm height.…”
Section: Methodsmentioning
confidence: 99%